Nutritional composition of silage from pearl millet cultivars with the inclusion of soy hulls (Revista Ciência Agronômica, 2017)
The nutritional composition of silages from the millet cultivars BRS 1501, ADR 500 and ADR 8010 wasevaluated with the inclusion of soy hulls at 0, 3, 6 and 10%. The experimental design was completely randomized in a 3 x 4factorial scheme with 3 replications. The dry matter content of the silages was affected by the inclusion of the soy hulls, rangingfrom 16.20% (ADR 8010) to 23.27% (BRS 1501) for the inclusion of 0 and 10% respectively. The levels of crude proteinranged from 9.46 to 10.79%, with significant differences between varieties being seen with the inclusion of 6% and 10% soyhulls. Inclusion of the hulls reduced the mineral matter content of the silages, with a change of 8.62% in the control treatment,up to an average of 6.38% at the level of 10%. The neutral (NDF) and acid (ADF) detergent fiber content did not differ withtreatment. The hemicellulose content differed with the level of soy hulls, and ranged from 22.65 to 26.18%. The cellulosecontent varied from 24.90% (ADR 500), with the inclusion of 6% soy hulls, to 29.80% (ADR 8010) with the inclusion of 10%hulls. The lignin content showed significant differences for the level of hull inclusion, ranging from 1.37% (ADR 8010) withthe inclusion of 10% hulls, to 3.71% (BRS 1501), found in the control treatment. The soy hulls increased the dry matter contentof silages from the cultivars under evaluation.